THE APPLICATION OF INNOVATIVE METHODS IN SPIRITUAL AND EDUCATIONAL ACTIVITIES - Akmal Sadretdinovich Ziyoyev,, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2023)
This article explores the application of innovative methods in spiritual and educational activities. The modern education system requires new approaches to moral and spiritual development, emphasizing the need for innovative pedagogical techniques. The paper examines the essence of spiritual and educational activities, their significance in character formation, and the role of modern methods in improving their effectiveness. Various innovative approaches, including interactive learning, digital technologies, and experiential education, are analyzed. Additionally, recommendations are provided for integrating these methods into educational institutions to enhance students' moral and ethical development.